2021
DOI: 10.2196/31056
|View full text |Cite
|
Sign up to set email alerts
|

Interventions Using Heart Age for Cardiovascular Disease Risk Communication: Systematic Review of Psychological, Behavioral, and Clinical Effects

Abstract: Background Cardiovascular disease (CVD) risk communication is a challenge for clinical practice, where physicians find it difficult to explain the absolute risk of a CVD event to patients with varying health literacy. Converting the probability to heart age is increasingly used to promote lifestyle change, but a rapid review of biological age interventions found no clear evidence that they motivate behavior change. Objective In this review, we aim to id… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 39 publications
(97 reference statements)
3
20
0
Order By: Relevance
“…This study also replicated several heart age effects found in reviews of previous research, in that it leads to a more negative emotional response, increased gist and verbatim knowledge of heart age, but not percentage risk, and reduced credibility, but is neutral for lifestyle change overall [ 60 , 61 ]. Our subgroup analyses suggest that more nuanced study designs are required to better understand the effects of heart age.…”
Section: Discussionsupporting
confidence: 81%
“…This study also replicated several heart age effects found in reviews of previous research, in that it leads to a more negative emotional response, increased gist and verbatim knowledge of heart age, but not percentage risk, and reduced credibility, but is neutral for lifestyle change overall [ 60 , 61 ]. Our subgroup analyses suggest that more nuanced study designs are required to better understand the effects of heart age.…”
Section: Discussionsupporting
confidence: 81%
“…Emerging evidence indicates that PHA could have potential benefits in clinical practice. 15 For example, the concept of (high) absolute cardiovascular risk is better understood by patients when expressed as PHA. 15 Furthermore, communicating patients’ absolute cardiovascular risk as PHA elicits more emotional impact and risk perception than absolute risk predictions.…”
Section: Discussionmentioning
confidence: 99%
“…We selected the Framingham risk score 7 to be consistent with previous research, as previous studies of the clinical usefulness 15 and distribution of PHA across multiple countries (including LMICs) 18 , 19 , 23 , 24 have used the Framingham risk score. We used the following variables to compute PHA in people without history of CVD 7 : sex, age (years), SBP, BMI, treatment for hypertension, smoking and diabetes status.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations